Effect of silver diamine fluoride on the prevention of erosive tooth wear in vitro. Issue 3 (May 2020) - Ainoosah, Sultan E.; Levon, John; Eckert, George J.; Hara, Anderson T.; Lippert, Frank
Highlights: The ability of silver diamine fluoride (SDF) to prevent erosion and erosion-abrasion was investigated in vitro. SDF was effective in preventing erosion on enamel and dentin. SDF was effective in preventing erosion-abrasion on dentin only. Abstract: Objectives: To investigate the ability of silver diamine fluoride (SDF) to prevent erosive tooth wear in enamel and dentin. Methods: SDF (38 %) was compared to deionized water (DIW, negative control), potassium fluoride (KF, fluoride control), silver nitrate (AgNO3, silver control), and fluoride varnish (FV, clinical reference) using erosion and erosion-abrasion cycling models. Bovine enamel and dentin slabs were embedded in resin blocks. Two resin blocks were glued to form study blocks (n = 8, per treatment), one for erosion and the other for the erosion-abrasion model. The blocks were treated once and then subjected to a five-day cycling model, with five daily citric acid erosive challenges (0.3 % citric acid/pH 2.6). Abrasion was performed using a toothbrushing machine with a medium-abrasive silica as abrasive (erosion-abrasion model only). Artificial saliva was used to remineralize the specimens after erosion/abrasion and as storage media between cycles. Surface loss (SL) was determined by non-contact profilometry. Data were analyzed using ANOVA (α = 0.05). Results: Both eroded-abraded enamel and dentin specimens exhibited significantly more SL in all treatment groups than the only eroded ones (p < 0.001). For dentin, both AgNO3 and DIW groups had significantly more SL than SDF, KF, and FV groups (p < 0.001), for both models. For enamel, specimens had more SL in both AgNO3 and DIW groups compared to SDF, KF, and FV groups, in the erosion model. When enamel specimens were subjected to erosion-abrasion, FV resulted in the least SL (p < 0.001). Conclusion: SDF was effective in reducing dental erosion on both substrates, but dental erosion-abrasion only on dentin. Clinical significance: SDF may become a viable intervention for ETW prevention in dentin (e.g. exposed roots) once its efficacy has been confirmed under clinical conditions.